The new encyclopedia of Southern culture. - Wood, Amy Louise, 1967- (New Encyclopedia of Southern Culture Ser., 2011)
Much of the violence that has been associated with the United States has had particular salience for the South, from its high homicide rates, or its bloody history of racial conflict, to southerners' popular attachment to guns and traditional support for capital punishment. With over 95 entries, this volume of The New Encyclopedia of Southern Culture explores the most significant forms and many of the most harrowing incidences of violence that have plagued southern society over the past 300 years. Following a detailed overview by editor Amy Wood, the volume explores a wide rang.